Anatomo-clinical aspects of acute appendicitis - Croci, Fabio; Gastambide, Carmelo; Pérez Penco, Ernesto; Cordal, Adriana (Cirugía del Uruguay, 1985)
On the experience of a series of 420 cases of opera• ted acute appendicitis in individuals over 14, authors discuss the anatomo-pathological, clinical, evolutive and prospective characeristics of lhis condilion in the light of !he appendicular topography. In said series, a 25% of the cases had retrocolic topography and the three verified cases of death occurred among them. (0.7%).